(3eMOOGJg hBKGQg GdGbJUGOjIs - (3CMeO CHh GdaJhM Ydj(B, (3GdfGbIs ((3GdGScfOjI(B:s (3ecJHI heWHYI GdGTYGY GdafjI(B,s, 2001)
(3eOi NGQLjI GdGfaGb GdOaGYj heMOOGJg, GdBKGQ GdGbJUGOjI ddGfaGb GdOaGYj(B.s
Keywords: (3GdCKGQ GdEbJUGOjIs; (3GdESJgdGcs; (3GdEfaGbs; (3GdOaGY GdhWfjs